2019
DOI: 10.1021/acsami.9b05013
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Bacteria Response by Piezoelectric Stimulation

Abstract: Bacteria are simple organisms with a remarkable capacity for survival by adapting to different environments, which is a result of their long evolutionary history. Taking into consideration these adapting mechanisms, this work now investigates the effect of electrically active microenvironments on bacteria and on how this stimulation may trigger bacteria growth inhibition or proliferation. Electrical microenvironments are generated via stimulation of a piezoelectric polymer with a mechanical cue, thus developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 45 publications
7
72
0
Order By: Relevance
“…Second, it is known that PVDF-based piezoelectric polymer membranes are capable of negatively affecting the Staphylococcus culture when under a dynamic load of the membrane, even in the absence of antibacterial agents [49]. Since in membranes containing 15 wt % of PVP the predominant conformation of VDF-TeFE macromolecules was the electrically active trans conformation ( Figure 2) and crystallites with characteristic ferroelectric properties predominate in the crystal structure (Figure 3), it can be assumed that the decrease in the concentration of pathogens in the wound and improved tissue regeneration is due to the piezoelectric properties of the formed membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Second, it is known that PVDF-based piezoelectric polymer membranes are capable of negatively affecting the Staphylococcus culture when under a dynamic load of the membrane, even in the absence of antibacterial agents [49]. Since in membranes containing 15 wt % of PVP the predominant conformation of VDF-TeFE macromolecules was the electrically active trans conformation ( Figure 2) and crystallites with characteristic ferroelectric properties predominate in the crystal structure (Figure 3), it can be assumed that the decrease in the concentration of pathogens in the wound and improved tissue regeneration is due to the piezoelectric properties of the formed membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Tuning frequency and amplitude of surface waves can control biofilm formation [85][86][87][88][89][90]92] Shear flows High shear flows lead to more compact biofilm formation and changes in its mechanical properties [48,92,93,103] Biofilms, sessile microbial communities embedded in EPS, also emerge on surfaces, but the conditions favourable for biofilm formation are distinct from those for swarming. Biofilms are prominent on solid-liquid, solid-air and liquid-air phase boundaries, and are recalcitrant to almost all types of biological and biochemical stresses.…”
Section: Mechanical Surface Wavesmentioning
confidence: 99%
“…On the other hand, the proliferation effect of bacteria has been observed at the surface of electrically polarized hydroxyapatite (Ueshima et al, 2002). Recent findings reported that bacterial cells behavior, which grow upon piezoelectric polymers, may be tailored according to the surface charge of the material and on the application of weak electrical field, promoted by a piezoelectric polymer under mechanical stimuli, demonstrating a different behavior between Gram-positive and Gram-negative cells (Carvalho et al, 2019). The Gram-positive bacteria seems not adhere to positively charged surface, as opposed to the negatively charged surface.…”
Section: Smart Materials and Active Surfaces For Tailoring Bacterial mentioning
confidence: 99%
“…The Gram-positive bacteria seems not adhere to positively charged surface, as opposed to the negatively charged surface. In the presence of an electrical stimuli, this strain shows a different behavior: the lower frequency promotes the antifouling and the higher stimulates the bacteria adhesion (Figure 6) (Carvalho et al, 2019).…”
Section: Smart Materials and Active Surfaces For Tailoring Bacterial mentioning
confidence: 99%
See 1 more Smart Citation